A large outbreak of measles in the West Midlands, England, 2017–2018: descriptive epidemiology, control measures and lessons learnt. (19th April 2021) - Mulchandani, R.; Sibal, B.; Phillips, A.; Suleman, S.; Banerjee, A.; Teagle, R.; Foulkes, S.; Spence, K.; Edeghere, O.
Abstract: In November 2017, eight confirmed measles cases were reported to Public Health England from a hospital in the West Midlands. A multidisciplinary Incident Management Team (IMT) was established to determine the extent of the problem and coordinate an outbreak response. Between 1 November 2017 and 4 June 2018, a total of 116 confirmed and 21 likely measles cases were linked to this outbreak; just under half (43%) were aged over 15 years of age. Fifty-five of the confirmed cases were hospitalised (48%) and no deaths were reported. At the start of the outbreak, cases were mostly individuals of Romanian origin; the outbreak subsequently spread to the wider population. Over the 8-month response, the IMT conducted the following control measures: extensive contact tracing, immediate provision of post-exposure prophylaxis, community engagement amongst specific high-risk groups, MMR awareness raising including catch-up campaigns and enhanced vaccination services at selected GP surgeries. Key challenges to the effective control measures included language difficulties limiting community engagement; delays in diagnosis, notification and appropriate isolation of cases; limited resources for contact tracing across multiple high-risk settings (including GPs and hospitals) and lack of timely data on vaccine coverage in sub-groups of the population to guide public health action.